Chemical experiment and its importance in teaching chemistry - SUBOTIN, Iurie (Journal of Social Sciences, 2019)
Chemistry is an experimental science that is based on theoretical process and finds its application in practical attempts in laboratory; it is based on experiment, as well as it is a method for scientific investigation, learning and evaluation. Having an experimental character, chemistry can not be taught, learnt and evaluated without practical experiments. The experiment is a didactic method through which trained people have the purpose to carry out a chemical or physical process or phenomenon, or to modify their standard conditions by introducing some new variables with the purpose to study them.